(untitled) (Proceedings of Southern Federal University. Philology, 2010)
Pivovarova I.A. Keywords: mytho-poetic space, artistic world, characters system, semantic oppositions. The structure of mytho-poetic space depicted in Kondratiev’s artistic world of prose is analysed in the article, functions of mytho-poetic space on the level of characters system (image system) and motive structure are specified and described. The author comes to the conclusion that Kondratiev’s artistic world deals with two types of space: natural and cultural, which are organized with the regard to semantic oppositions which are formulated in the mythological system.